Application of the word2VEC algorithm for clinical diagnosis determination - Uzeyir Gurbanli (Institute of Information Technology, Ministry of Science and Education of the Republic of Azerbaijan, 2025)
The article examines the use of Natural Language Processing technologies in modern medicine for knowledge acquisition and the implementation of decisionmaking methods. The application of information technology in healthcare has become one of the main requirements of the modern era. Enhancing the quality and accessibility of medical services necessitates the utilization of modern technologies, mathematical methods, and the capabilities of artificial intelligence, alongside the development of comprehensive information systems.